The Impact of Network Centralization on Relational Capital - Osman, Lokhman Hakim Bin (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
With an increasing degree of connections among firms forming network of economic activities, it is timely to assess the potential of these upon embedded firms. This article presents empirical evidence to that end. It distinguishes between decentralized and centralized network structure that illustrate the difficulties encountered in managing an inter-firm network structure. Although considerable studies has been performed in network issues affecting firms performance, very few research analyse the complicating attributes of a centralized network structure on its effects on firms performance. Thus this article described different attributes of the centralized network and its effects on firms